2018
DOI: 10.1371/journal.pone.0203930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity and reliability of a visual dental scale for detection of periodontal disease (PD) in non-anesthetized dogs (Canis familiaris)

Abstract: Periodontal disease is one of the most common conditions affecting companion dogs. The objectives of this cross-sectional study were: to determine 1) the agreement between visual assessments (VA) of periodontal disease (PD) performed on awake dogs and the reference standard (RS) of a dental examination and radiographs performed with the dog under general anesthesia, and 2) inter-rater reliability (IRR) for two individuals performing VAs of PD on the same dogs. One hundred and eight dogs were recruited from thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
1
19
0
4
Order By: Relevance
“…The removal can be done by mechanical (Brushing, scaling, ultrasonic scaling, and dental chew) and chemical (chlorhexidine gluconate, and special diet) means for the prevention and control of periodontal disease [1,4,5,9,10]. The use of dental chews of varied shapes and sizes with or without an anti-calculus agent has been demonstrated as one of the easiest methods for removal of supragingival plaque accumulation [5,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The removal can be done by mechanical (Brushing, scaling, ultrasonic scaling, and dental chew) and chemical (chlorhexidine gluconate, and special diet) means for the prevention and control of periodontal disease [1,4,5,9,10]. The use of dental chews of varied shapes and sizes with or without an anti-calculus agent has been demonstrated as one of the easiest methods for removal of supragingival plaque accumulation [5,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Redness, inflammation, receding, or hyperplasia of gingiva in the presence of dental calculus are recognized signs of PD in visual dental examinations [ 29 ]. However, previous studies showed that GR could occur in the absence of plaque and inflammatory cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visual assessment of PD in non-anesthetized dogs showed moderate agreement with the reference standard diagnosis, based on use of periodontal probing and dental radiography in anesthetized animals (41.57% of agreement and weighted kappa = 0.42, 95% confidence interval: 0.29–0.55) [ 29 ]. Additionally, when experienced dentists perform these visual assessments, substantial inter-examiner reliability is achieved (61.02% of agreement and weighted kappa = 0.63, 95% confidence interval: 0.49–0.76) [ 29 ]. Therefore, visual assessment could be useful to detect animals needing dental care, when a larger number of dogs must be examined out of clinic facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo, (Bauer et al, 2018), avaliaram a confiabilidade de uma avaliação de escala de doença periodontal em cães não anestesiados, reforçaram a ideia de que o exame oral em um cão acordado é uma ferramenta de triagem útil, mas não deve ser considerada uma avaliação completa. Dessa forma, com o animal anestesiado, deve-se observar as mucosas detalhadamente, fazendo uma avaliação individual de cada dente, avaliando forma, posição, estrutura de suporte, cálculo dentário, profundidade e se há presença de restos de alimentos no sulco gengival, se há presença de hiperplasia gengival (HG), retração gengival (RG) ou se apresenta ulcerações, deve-se também notar quanto a presença de exsudato purulento (Gouveia, 2016;Valadares, 2018).…”
Section: B C Aunclassified